Non-territorial self-governance of national minorities in Serbia: Legal framework and its shortcomings on the light of the decision of the Constitutional Court - Korhec Tamaš (Anali Pravnog Fakulteta u Beogradu)
The self-governance of national minorities might be provided on territorial and non-territorial (personal) bases. It is institution of the public law by which the effective participation of national minorities in public affairs is ensured in a particular State. In legal order of the Republic of Serbia the self-governance of national minorities is guaranteed by the Constitution and it is realized throe elected national councils of national minorities, established first in 2002. National councils and their legal regulation generated political and legal disputes; consequently several initiatives were launched for the constitutional review of the law in 2010 and 2011. This paper is devoted to the analyses of this Decision enacted in 2014. On the one hand, the Constitutional Court authoritatively resolved some open constitutional disputes and contributed to the better understanding of this institution, but on the other hand, because of some shortcomings and controversies in reasoning created further uncertainties concerning the actual legal framework of self-governance of national minorities in Serbia.